ANALISIS DAMPAK FAKTOR MAKRO EKONOMI PADA SAHAM JAKARTA ISLAMIC INDEX - faizin, moh; Oktawati, Nurul Rizki (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.09.N0.12.TAHUN 2020, 2020)
The Jakarta Islamic Index consists of 30 shares of sharia-based companies. From a macroeconomic level, stock prices can be determined by exchange rates, exchange rates, the amount of money spent and interest rates. The purpose of this research is to analyze the variables of exchange rates, exchange rates, the amount of money converted and interest rates on the JII stock index. Using secondary data, and observation methods for the period 2010 to 2019. This study uses multiple linear regression and SPSS 21 software. But interest rates and values ??are not significantly significant. Then the independent variable is significant with respect to the dependent variable.